Long-term offspring epilepsy outcomes following planned assisted homebirth versus hospital birth - Matti Sillanpää; Maiju M. Saarinen; Päivi Polo-Kantola (Foundation of Epileptology, 2022)
Background
Planned homebirth is an option available to a small minority of expecting mothers. Compared with hospital births, long-term risks of homebirths are poorly known.
Aim
To study very long-term outcome for death, seizure remission, and other neurological long-term comorbidities
Material and Methods
A cohort of virtually all children (n = 230) in a geographically defined area with onset of epilepsy in or active epilepsy diagnosed prior to 1961–1964, and prospectively followed-up for 50 years.
Results
The proportion of homebirths was 16% in blue collar families and 2% in white collar families (p = 0.007). No significant differences between homebirths and hospital births were found in the frequencies of either abnormal pregnancy (27% vs 27%, p > 0.99) or abnormal birth (32% vs 35%, p = 0.82). Premature mortality following homebirths was non-significantly higher than that following hospital births (41% vs 27%, p = 0.13). Homebirth did not significantly affect 5-year (38% vs 40%) or 10-year (38% vs 37%) remission. Neither was homebirth alone associated with neurological morbidity (2.1, 0.82–6.1, p = 0.137).
Conclusion
Homebirth is an observable but non-significant risk factor of offspring mortality and neurological morbidity of an offspring with epilepsy. Blue collar families preferred homebirth to hospital birth for reasons which are not fully understood. Further research is needed in a prospective setting by applying modern standards of early identification of risk pregnancies and deliveries, carefully monitoring the health of expecting mothers, and anticipating referral to specialist services according to medical needs.